Prevalence and risk factors of burnout among community pharmacists in Saudi Arabia: a cross-sectional study - Hijri, Abdulrahman M.; Alzahrani, Fahad; Madkhali, Osama A.; Ali, Majid; Alaqil, Mazen A.; Salami, Riyadh M.; Madkhali, Yaseen A.; Almalki, Abdulrahman A.; Hassany, Emad H.; Ahmed, Asma M.; Khubrani, Khalid H.; Alsubaie, Nasser M.; et al. (Frontiers in Public Health, 2025)
BackgroundBurnout among healthcare professionals impacts patient care quality and healthcare systems. While extensively studied across various healthcare sectors, burnout among community pharmacists in Saudi Arabia remains underexplored despite their expanding roles in healthcare delivery.MethodsThis cross-sectional study utilized an online survey with the validated Maslach Burnout Inventory-Human Services Survey (MBI-HSS) to assess burnout across three dimensions among community pharmacists in Saudi Arabia from December 2024 to March 2025. Multiple regression analysis identified factors associated with burnout.ResultsAmong 408 community pharmacists (mean age 28.07 ± 3.75 years, 72.8% male), high levels of burnout were prevalent: 65.9% exhibited high emotional exhaustion (EE) (mean 35.50 ± 14.40), 64.5% showed high depersonalization (DP) (mean 14.66 ± 8.26), and 66.2% demonstrated low personal accomplishment (mean 29.34 ± 11.16). Sales pressure frequency was the strongest predictor of EE (β = 0.312, p < 0.001) and a significant predictor of DP (β = 0.218, p < 0.001). Saudi nationality was strongly associated with both EE (β = 0.267, p < 0.001) and DP (β = 0.298, p < 0.001). Years of experience showed protective effects against burnout dimensions. Pharmacists experiencing constant sales pressure had 4.23 times higher odds of high EE (95% CI: 2.18–8.21, p < 0.001).ConclusionCommunity pharmacists in Saudi Arabia experience alarmingly high burnout levels, particularly among Saudi nationals, those facing constant sales pressure, practitioners with less experience, and those managing high patient volumes. These findings highlight the urgent need for workplace interventions, policy changes, and support systems focusing on reducing commercial pressures, optimizing workload distribution, and providing targeted support for vulnerable subgroups.